BACE1-Dependent Neuregulin-1 Signaling: An Implication for Schizophrenia - Zhang, Zhengrong; Huang, Jing; Shen, Yong; Li, Rena (Frontiers in Molecular Neuroscience, 2017)
Schizophrenia is a chronic psychiatric disorder with a lifetime prevalence of about 1% in the general population. Recent studies have shown that Neuregulin-1 (Nrg1) is a candidate gene for schizophrenia. At least 15 alternative splicing of NRG1 isoforms all contain an extracellular epidermal growth factor (EGF)-like domain, which is sufficient for Nrg1 biological activity including the formation of myelin sheaths and the regulation of synaptic plasticity. It is known that Nrg1 can be cleaved by β-secretase (BACE1) and the resulting N-terminal fragment (Nrg1-ntf) binds to receptor tyrosine kinase ErbB4, which activates Nrg1/ErbB4 signaling. While changes in Nrg1 expression levels in schizophrenia still remain controversial, understanding the BACE1-cleaved Nrg1-ntf and Nrg1/ErbB4 signaling in schizophrenia neuropathogenesis is essential and important. In this review paper, we included three major parts: (1) Nrg1 structure and cleavage pattern by BACE1; (2) BACE1-dependent Nrg1 cleavage associated with schizophrenia in human studies; and (3) Animal studies of Nrg1 and BACE1 mutations with behavioral observations. Our review will provide a better understanding of Nrg1 in schizophrenia and a potential strategy for using BACE1 cleavage of Nrg1 as a unique biomarker for diagnosis, as well as a new therapeutic target, of schizophrenia.